Between persistent crises and dilemmas: an analysis of student permanence programs in Brazilian federal universities - Borges, Eduardo Henrique Narciso; Gouvea, Adriane Pereira; Barbosa, Maria Ligia de Oliveira (Plural, 2022)
In recent years, Brazilian higher education has faced numerous problems related to the processes of economic turbulence, recession cycles and cost reduction for the maintenance of institutions, a horizon aggravated by the eff ects of the COVID-19 pandemic. This scenario rekindled the discussion about the importance of expansion and impasses for the maintenance of university student permanence programs. This paper aims to analyze, from a literature review and analysis of secondary data, the construction of public policies of assistance and student permanence in the country, by discussing its effects on student trajectories and addressing the problems currently faced aiming at permanence, completion of courses and equity within the system.